(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
Ensérune is a major site in Mediterranean Protohistory. As a "Carrefour des civilisations", it is at the heart of exchanges and debates that have built up a discipline throughout the 20th century, but which must now be re-evaluated in the light of new research perspectives, particularly from the global consideration of all the data available on and around the oppidum. This new dynamic has been at work on this site for the past few years. This article aims to present the main aspects.